1975
DOI: 10.1111/j.1365-2818.1975.tb04533.x
|View full text |Cite
|
Sign up to set email alerts
|

The observation of crystalline materials in the scanning electron microscope (SEM)

Abstract: Contrast effects from electron channelling in crystalline solids can be observed in the scanning electron microscope by the correct choice of operating conditions. The crystallographic symmetry and orientation of specimen areas as small as 1 pm in diameter can be determined, and detailed quantitative information obtained about the density, nature and position of defects contained within the crystal structure. The backscattered, absorbed current and transmitted electron signals may all be used. With anticipated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Although ~ome recrystallization has apparently occurred at 750~ the patterns are of very poor quality when compared to those from u n i mplanted material. These results seem to be inconsistent with other published results (6, 7), which indicate that major reordering of amorphous I n P occurs in the range from 450 ~ to 500~ It has been reported that, in addition to the degree of crystallinity, factors such as lattice strain of a few percent can result in loss of resolution or contrast in electron channelling patterns (9). For the Mg implants discussed here, lattice strain may be significant and could therefore be responsible for the discrepancy between our results and those of others regarding the recrystallization temperature for amorphous InP.…”
Section: Resultscontrasting
confidence: 91%
“…Although ~ome recrystallization has apparently occurred at 750~ the patterns are of very poor quality when compared to those from u n i mplanted material. These results seem to be inconsistent with other published results (6, 7), which indicate that major reordering of amorphous I n P occurs in the range from 450 ~ to 500~ It has been reported that, in addition to the degree of crystallinity, factors such as lattice strain of a few percent can result in loss of resolution or contrast in electron channelling patterns (9). For the Mg implants discussed here, lattice strain may be significant and could therefore be responsible for the discrepancy between our results and those of others regarding the recrystallization temperature for amorphous InP.…”
Section: Resultscontrasting
confidence: 91%
“…It is supposed that too many SE2s are collected by the In‐Lens SE detector. SE2s are generated by BSEs, which are quite sensitive to the grain orientations leading to the channelling contrast (Joy, ; Canovic et al ., ). In addition, the In‐Lens SE detector may also collects a small portion of low‐angle BSEs, which will directly contribute to the channelling contrast.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the In‐Lens SE detector may also collects a small portion of low‐angle BSEs, which will directly contribute to the channelling contrast. Because the slice‐and‐view process always creates clean surface for SEM, channelling contrast could be visible (Joy, ).…”
Section: Resultsmentioning
confidence: 99%
“…A major aspect of this study was to monitor the local texture and its changes, during this grain growth/migration process, using the diffraction signals available through the relatively new electron back scattering (EBS) diffraction technique now becoming incorporated into SEM (e.g. Joy, 1975;Randle er al., 1988). This technique, EBS (Fig.…”
Section: G R a I N G R O W T Hmentioning
confidence: 99%